2015
DOI: 10.1016/j.physbeh.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early-onset voluntary exercise on adult physical activity and associated phenotypes in mice

Abstract: The purpose of this study was to evaluate the effects of early-life exercise on adult physical activity (wheel running, home-cage activity), body mass, food consumption, and circulating leptin levels in males from four replicate lines of mice selectively bred for high voluntary wheel running (High Runner or HR) and their four non-selected control (C) lines. Half of the mice were given wheel access shortly after weaning for three consecutive weeks. Wheel access was then removed for 52 days, followed by two week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 67 publications
2
25
2
Order By: Relevance
“…However, we did find line- and sex-specific effects. Specifically, maternal WD increased wheel running for female offspring of HR line 7, which emphasizes our previous findings that the replicate HR lines have undergone somewhat different evolutionary paths under the same selection regime [4648]. A sex-specific effect was also found in a study of rats with maternal high-fat diet, which reported less active male and more active female offspring when given free wheel access for one week [8].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…However, we did find line- and sex-specific effects. Specifically, maternal WD increased wheel running for female offspring of HR line 7, which emphasizes our previous findings that the replicate HR lines have undergone somewhat different evolutionary paths under the same selection regime [4648]. A sex-specific effect was also found in a study of rats with maternal high-fat diet, which reported less active male and more active female offspring when given free wheel access for one week [8].…”
Section: Discussionsupporting
confidence: 73%
“…Although HR lines experienced the same directional selection, each replicate line (and sexes within lines) differed in response time to the selection pressure and mean voluntary wheel running [45], as well as other phenotypes [30, e.g., 37, 46]. Thus, the replicate HR lines have had “multiple solutions” [47] and may be expected to differ in response to manipulation of maternal diet.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evidence has explored whether other traits related to energy balance and physical activity are correlated with or influence SPA. For example, aerobic capacity does not correlate with SPA [56] while basal metabolic rate does [57], and the evidence is still mixed as to the effects of voluntary exercise on SPA [5861]. Future challenges include the accurate measurement of SPA, its different components and NEAT, the possibility of measuring SPA and NEAT in group housed animals, and accurate comparison of the physiological effects and mechanisms of SPA between males and females.…”
Section: Animal Models Of Spa and Obesitymentioning
confidence: 99%
“…Readings are then averaged over a one-minute interval and reported using arbitrary units. We used a similar setup and calibration procedure as previously reported (Acosta et al 2015; Copes et al 2015). HCA was measured for 23 hours per day and all analyses were performed using a measure of sensor sensitivity as a covariate (Acosta et al 2015; Copes et al 2015).…”
Section: Materials and Proceduresmentioning
confidence: 99%